(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
The present case describes the clinical & radiographic outcome of a Portland Cement pulpotomy. The 5 years old girl presenting extensive carious exposure in her mandibular left 2nd deciduous molar and was suffering pain in her left lower jaw only on exposure to cold for last 2 days. She was ultimately diagnosed clinic-radio-graphically as a case of irreversible pulpitis. Coronal pulpotomy procedure was carried out in the responsible tooth and Portland cement (PC) was applied as a medicament after pulpotomy. At the 3 & 6-months follow-up appointments, treated tooth was asymptomatic clinically and radiographic examinations revealed no sign of periradicular pathosis in the pulpotomized teeth. Additionally, the formation of a dentin bridge immediately below the PC in the treated tooth was confirmed by RVG and CBCT.